SUPERVISI PENDIDIKAN ERA TEKNOLOGI 5.0 - Mahlopi Mahlopi (TARBIYATUL ILMU: JURNAL KAJIAN PENDIDIKAN, 2025)
Educational supervision is the best teaching and learning process, which involves teachers and students, through a series of actions, guidance and direction. Improvement of the teaching and learning process whose achievements. Supervision comes from two words in English, namely super and vision. Super means above and vision means to see, still allied with inspection, inspection and supervision, and surveillance in the sense of activities carried out by superiors, people in positions above, leadership of things that are below them. The development of science and technology (IPTEK) requires people to learn continuously. Especially teachers who have the task of educating and teaching. A little careless in learning will be left behind with developments, including the students being taught. Technology is a tool that facilitates the learning process. According to Nasution (1984) educational technology is the development, application of assessment systems, techniques and tools to improve and enhance human learning achievement.